VARIABEL-VARIABEL YANG MEMPENGARUHI FLUKTUASI NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA SERIKAT PASKA PENETAPAN SISTEM MENGAMBANG MURNI (Pendekatan Dua Langkah Model Koreksi Kesalahan dari lnsukindro) - Anwar, Nurul; Kurniawati, Apriana Eka (JURNAL BISNIS STRATEGI, 2007)
This tesesrcn entitled ''Variables Influencing The Exchange Rate of Rupiah after Applic2tion of Pure Floating Exchang'J rate System (Two Stage lnsukindro-Error Correction MJdel )". This study aimed to analyze variablesthat influence the rupiah exchange rate for the period of third quarter uf 199 7 to second quarter of 2006.The study used Two Stage lnsukindro-Error Correction Model (lnsukindm ECM). Tl1is modei was completed by test of classical assumption and validation test of Insukindro-ECM. To approaches the problem, the studyutilized two :1pproaches i,e, Bc1/ance of payment approach and Monetaryapproach. The exchange rate of rupaih ini this study was expressed by The Real Effective Exchange rate (REER). Variables used in Monetary approach are; the Expectstton of exchange rate (Rp/USD), the Difference of interestrate, Relative price rate, Nei'toreign assets, real Gross domestic Product(GDP), Money supply, and Sterilized foreign exchange intervention shocks.Variables in The Balance of payment approach are; the Expectation of ,exchange rate (Rp/USD), the Difference of interest rate, Relative price rate,Import, Oil price, Capital flight of portfolio, and GovemmentÂ» external debt shocks. To compare the ability of prediction between two approaches the study utilized Root mean square error (RMSE), mean absolute error (MAE),and mean absolute percentage eror (MAPE).The research result shows that according to Monetary approach the expectation of exchange rate and the difference of interest rate significantly influenced the exchange rate of rupiah in the long run. Based on the Balance of Payment approach the expectation of exchange rate and import variables significantly influenced the exchange rate of rupiah in the sort run, and oil price variable significantly influenced the exchange rate of rupiah in the long run.Using Two Stage lnsuldndro-Error Correction Model (lnsukindro ECM) thestudy shows that sterilized foreign exchange, intervention, and government's external debt shocks significantly influenced the exchange rate of rupiah either in the sort run and in the long run. Based on the parameters of RMSE, MAE, and MAPE this study shows that the Balance of Payment approach were more accurate than that of Monetary approach in term of predicting the fluctuation of exchange rate of rupiah after implementing pure floating exchange rate system in Indonesia.